Response of Biofertilizer Application and Alkali Supplement Fertilizer on the Growth and Yield of Curly Red Chili (Capsicum annuum L.) - Devi Puspita Amartha Yahya; Kus Hendarto; Fitri Yelli; R.A. Diana Widyastuti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
This research aimed to determine the effect of biofertilizer application and alkali supplement fertilizer on the growth and yield of chili (Capsicum annuum L.) This research is arranged in a randomized block design (RBD) consisting of two factors and three replications. The first factor is biofertilizer with three levels, i.e., H0=without biofertilizer; H1= dose of 4 ml/plant; H2= dose of 8 ml/plant. The second factor is alkali supplement fertilizer with three levels, i.e., P0=without alkali supplement fertilizers; P1= dose of 0,05 gr/plant; P2= dose of 0,1 gr/plant. The results showed that the growth variable did not have a significant interaction effect between biofertilizer and alkali supplement fertilizer. Meanwhile, in production variables, there are interaction effects between the application of biofertilizers and alkali supplement fertilizer in variables of number of flowers, number of fruit consumption, and fruit weight per plant. The biofertilizer application with a dose of 8 ml/plant accompanied by alkali supplement fertilizers dose of 0,1 gr/plant resulted in the highest fruit weight, 436.70 grams/plant. The biofertilizer application of 8 ml/plant produced 402.12 grams/plant3, while the application of alkali supplement fertilizer with a dose of 0,1 gr/plant produces chili production of 400.51 grams/plant.Keywords: alkali supplement fertilizer, biofertilizer, chili